- (cond <clause> <clause> ...)syntax
Syntax: Each <clause> should be of the form
(<test> <expression> ...)
where <test> is any expression. Alternatively, a <clause> may be of the form
(<test> => <expression>)
The last <clause> may be an "else clause," which has the form
(else <expression> <expression> ...).
Semantics: A cond expression is evaluated by evaluating the <test> expressions of successive <clause>s in order until one of them evaluates to a true value (see the section about booleans below). When a <test> evaluates to a true value, then the remaining <expression>s in its <clause> are evaluated in order, and the result(s) of the last <expression> in the <clause> is(are) returned as the result(s) of the entire cond expression. If the selected <clause> contains only the <test> and no <expression>s, then the value of the <test> is returned as the result. If the selected <clause> uses the => alternate form, then the <expression> is evaluated. Its value must be a procedure that accepts one argument; this procedure is then called on the value of the <test> and the value(s) returned by this procedure is(are) returned by the cond expression. If all <test>s evaluate to false values, and there is no else clause, then the result of the conditional expression is unspecified; if there is an else clause, then its <expression>s are evaluated, and the value(s) of the last one is(are) returned.
(cond ((> 3 2) 'greater) ((< 3 2) 'less)) ===> greater (cond ((> 3 3) 'greater) ((< 3 3) 'less) (else 'equal)) ===> equal (cond ((assv 'b '((a 1) (b 2))) => cadr) (else #f)) ===> 2